Kontribusi kebiasaan dan lingkungan belajar terhadap hasil belajar matematika di SMP Negeri 30 Batam tahun pelajaran 2019/2020 - Peramita; Hasibuan, Nailul Himmi (Jurnal Pendidik Indonesia, 2021)
This study aims to analyze the extent to which study habits and learning environment contribute to the mathematics learning achievement of 8th-grade students at SMP Negeri 30 Batam in the 2019/2020 Academic Year. This research employs a correlational approach with a population of 346 8th-grade students at SMP Negeri 30 Batam and a sample size of 186 students. The sampling technique used is Simple Random Sampling. The instrument utilized in this study is a questionnaire. The research findings reveal several significant points: (1) There is a significant relationship between study habits and the learning achievement of 8th-grade students at SMP Negeri 30 Batam, with a contribution of study habits amounting to 86.67%; (2) The learning environment also holds a significant contribution to the learning achievement of 8th-grade students at SMP Negeri 30 Batam, with a contribution of 33.98%; (3) In this context, study habits and the learning environment together contribute 86.67% to the learning achievement of 8th-grade students at SMP Negeri 30 Batam. The resulting regression model is Y = 1.024X1 - 0.21X2 - 12.37, illustrating the relationship between study habits (X1) and the learning environment (X2) with students' learning achievement (Y).